Kísérlet a jogösszehasonlítás mint diszciplína bevezetésére a debreceni egyetemen (1927) - P. Szabó, Béla (Gerundium, 2010)
An Attempt to Introduce Comparative Law as a Self-Contaiained Discipliline at the University of Debrecen (1927) At the beginning of 1927, Géza Marton, professor of law in Debrecen, prepared a position paper with regard to the chances of introducing comparative law as a separate subject at the school of law. Commenting on this event, the present study—which thematically pertains to the history of the old law school—offers data concerning the history of comparative law, with proper priority given to disciplinary and educational ramifications of this area of study formerly both parly boosted, partly neglected int he history of Hungarian learning. Prior to the publication of and the comments on Professor Marton’s original text, the study reiterates some memorable facts and aspects of Hungarian scholarly and educational history, interlarding these with some less well-known data and points of interest.